ALGORITHM OF PERSONAL STYLE: A SYSTEMATIC APPROACH TO CREATING INDIVIDUAL LOOKS BASED ON MORPHOLOGY, COLOUR TYPE, AND BEHAVIOURAL PATTERNS - Kostogryz, Maryna (Global Prosperity, 2026)
Personal styling relies on three categories of client data (body morphology, colour characteristics, and behavioural preferences), yet practitioners typically evaluate these in isolation, producing recommendations that optimise for one parameter while inadvertently creating conflicts with the others. A silhouette chosen for proportional balance may arrive in a colour temperature that clashes with the client’s complexion; a palette aligned with seasonal colour analysis may be rejected because it contradicts the client’s psychological comfort zone. This study proposes a formalised decision-making algorithm that accepts all three parameters as simultaneous inputs, assigns each a weighted score, and generates an integrated output termed the "style formula." Body morphology is reconceptualised from categorical labels (hourglass, rectangle) to continuous dimensional scores (shoulder-hip ratio, waist definition index, vertical proportion). Seasonal colour analysis is similarly translated from discrete seasonal types to a three-axis coordinate system (hue temperature, value contrast, chroma level). Behavioural patterns are captured through a composite of personality traits, daily lifestyle distribution, and aesthetic tolerance. A weighted decision matrix resolves inter-parameter conflicts by adjusting parameter priority according to the client’s stated goals. Testing across the author’s consulting records (200+ female clients, 2016 to 2025) indicates that clients whose style was built through the three-parameter algorithm retained 78% of recommended wardrobe items in active use after six months, compared to 43% retention among clients styled through single-parameter approaches. Findings suggest that multi-parameter integration reduces both wardrobe waste and client dissatisfaction.